Hypoglycemic activity of fruiting body extracts from Pycnoporus sanguineus (L.: FR.) Murrill mushroom - Tuong, Tran Duc; Chu, Duong Xuan; Dieu, Bui Thi Minh (Academia Journal of Biology, 2018)
Alpha-amylase and α-glucosidase are two main enzymes involved in carbohydrate metabolism. Inhibition of α-amylase and α-glucosidase can be said as an effective treatment for delaying the absorption of glucose after meals in people with diabetes mellitus. The objective of the this study is to provide an in vitro evidence for the potential hypoglycemic activity via inhibitory activity of the ethanolic and aqueous extracts from fruiting bodies of Pycnoporus sanguineus mushroom on                      α-amylase and α-glucosidase enzymes. Alpha-amylase and α-glucosidase inhibitory activities of ethanolic and aqueous extracts from P. sanguineus fruiting body were examined in a dose-response manner. Acarbose was used as a positive control and the results showed that the ethanolic extract of P. sanguineus possessed strong inhibitory activity on α-amylase and α-glucosidase with IC50 values of 97.08 and 92.60 μg/mL, respectively. The aqueous extract also exhibited moderate activity against α-amylase and α-glucosidase with IC50 values of 150.15 and 102.29 μg/mL, respectively. Which was signiﬁcantly lower than that of acarbose with IC50 values of 85.12 and 68.36 μg/mL, respectively. The degree of α-amylase and α-glucosidase inhibition was correlated with the dose of inhibitors. From these results Pycnoporus sanguineus possesses high potential in lowering blood glucose level, reduced insulin resistance and the risk of diabetic-related complications.